Factors affecting job satisfaction among job oder government workers in a post-pandemic setting in Tacloban City - Bobier, Maria Alaine Stefani R.; Butastas, Angel P.; Edradan, Rey E.; Parac, Patricia T.
The COVID-19 pandemic fundamentally reshaped workplaces, prioritizing work-life balance and accelerating the use of remote work and digital tools. However, for job order government workers, who lack job security and benefits, the pandemic presented unique challenges. As we move towards a post-pandemic world, it is critical to ensure the job satisfaction of these essential workers. This study explored the factors affecting job satisfaction among job order government workers in a post-pandemic setting in Tacloban City. Researchers employed a descriptive quantitative approach, surveying 266 workers focusing on job security, organizational culture, salary and benefits, supervision, training and development, and work environment. The analysis revealed that the factors affect job satisfaction, with supervision having the strongest effect. Interestingly, salary and benefits were the least affecting factor among all. Furthermore, the study found that factors affecting job satisfaction varied depending on the workers' age, gender, educational attainment, and length of service. Recommendations include enhanced supervisory training, improved work environments, measures to ensure job security and competitive salaries and benefits for older workers, promotion of professional development opportunities for mid-career employees, and recognition of organizational culture. Additionally, the study suggests the continued evaluation of job satisfaction among job order government workers. By implementing these initiatives, policymakers can create a government workspace that addresses the diverse needs of job order government workers, fostering job satisfaction.